SORPTION OF URANIUM(VI) ONTO PHYLLITE - Arnold T.; Zorn T.; Bernhard G.; Nitsche H. (My University, 1998)
The sorption of U(VI) on phyllite and on its main mineral constituents, muscovite, quartz, chlorite, and albite feldspar was studied in individual batch experiments at ambient pressure from pH 3.5 to 9.5. The ionic strength was held constant at 0.1 M (NaClO4 solution). An uranium concentration of 1x10-6 M, a size fraction of 63-200 μm and a solid solution ratio of 0.5 g/40 ml were used. The study showed that sorption of uranium on the various mineral surfaces had its maximum at near neutral pH range. It further showed that the maximum amount of uranium sorbed onto each individual mineral was different and ranged from 48% of the initially added uranium for quartz, 58% for albite, 70% for muscovite and chlorite, to 97% for phyllite. From this, we conclude that none of the main mineral constituents of phyllite is dominating the sorption behaviour of uranium onto phyllite, but instead an additional component, minor in mass and volume, significantly influences the uranium sorption onto phyllite. Based on a 3% increase in the Fe(III) concentration during the batch experiments, detected by Mossbauer spectroscopy, and the formation of a slight reddish-brownish colour of the investigated powder at the end of the batch experiments, we expect that this additional component is the iron mineral ferrihydrite. Its formation is due to alteration reactions occurring in the course of the batch experiments. We have modelled our U(VI) sorption results onto phyllite with the Diffuse Double Layer Model assuming the formation of surface complexes between the ferrihydrite surface and aqueous uranium. With this model we were able to describe our uranium sorption data on phyllite.
Keywords: PHYLLITE; FERRIHYDRITE; SORPTION; URANIUM